Hepcidin Protects Neuron from Hemin-Mediated Injury by Reducing Iron - Zhou, Yu-Fu; Zhang, Chao; Yang, Guang; Qian, Zhong-Ming; Zhang, Meng-Wan; Ma, Juan; Zhang, Fa-Li; Ke, Ya (Frontiers in Physiology, 2017)
Hemin plays a key role in mediating secondary neuronal injury after intracerebral hemorrhage (ICH) and the cell toxicity of hemin is thought to be due to iron that is liberated when hemin is degraded. In a recent study, we demonstrated the iron regulatory hormone hepcidin reduces brain iron in iron-overloaded rats. Therefore we hypothesized that hepcidin might be able to reduce iron and then protect neurons from hemin or iron-mediated neurotoxicity in hemin-treated neuronal cells. Here, we tested the hypothesis and demonstrated that ad-hepcidin and hepcidin peptide both have the ability to suppress the hemin-induced increase in LDH release and apoptotic cell numbers, to reduce cell iron and ferritin contents, and to inhibit expression of transferrin receptor 1, divalent metal transporter 1 and ferroportin 1 in hemin-treated neurons. We conclude that hepcidin protects neuron from hemin-mediated injury by reducing iron via inhibition of expression of iron transport proteins.